Interaction Provenance-Age in 52 provenances of Pinus pinaster Ait. in Spain - Alia, R.; Gil, L.; Pardos, J. A.; Catalan, G. (Forest Systems, 1991)
The paper present results of an all range Pinus pinaster provenances study in Spain (42 Spanish, 2 Portuguese, 5 French and 1 Italian provenances), conducted in a four-replicated complete block design provenance test. Height growth for each provenance is analized at 1, 5, 14 and 18 years after planting. Comparisons of height at different ages show that selection of best provenances at 18 years old could be made at 5 years old, if the number of provenances is not too small (> 10 p. 100). Height growth at different ages is also studied like a provenance-site interaction. Joint regression analysis show a geographical distribution of provenances using two parameters: Provenance height at 5 years old and regression coefficient of the provenance height on the height mean of the test (bi).